Learning to teach contextualized problem-solving in a non-calculus mathematics pathway. (2nd May 2018) - Golding, Jennie; Smith, Cathy; Blaylock, Mick J
Abstract: We report on the professional learning of a small purposive sample of teachers beginning to teach an English post-16 mathematics course centred around contextualized problem-solving. We describe their accounts of change, their intentions and justification for those and how development was supported. The demands of the course require 'boundary crossing' between contexts and mathematics that was novel for these teachers and their students, and learning to teach for such approaches is known to be demanding. By drawing on peer support and their own robust subject knowledge, though, these teachers were able to accommodate change to classroom authority and expertise, attention to students' relationship with mathematics, longer-term planning sequences and growth in their own management of uncertainty within the classroom.